Experiment as a research method for investigating the effectiveness of drama in EFL Higher Education: A systematic review - Kolar, Miroslav; Sándorová, Zuzana (Glottodidactica, 2025)
The shift towards communicative teaching has led to the need of developing innovative approaches to teaching English as a foreign language. Among them, drama methodologies have gained increasing attention for their ability to enhance language learning efficiency. Although research indicates a positive contribution of drama to language learning, its application in university education remains largely unexplored. This study addresses this gap by systematically reviewing recent studies on drama techniques in higher education EFL classrooms and summarising experimental research trends and limitations in this context. Following the search in Scopus and Web of Science databases, 11 studies were identified according to inclusion and exclusion criteria for qualitative analysis. The results revealed an overall positive influence of drama on language classrooms. However, certain limitations were revealed, and more rigorous empirical studies are needed. By addressing these gaps, this review provides valuable insights. It proposes directions for future research, aiming to expand empirical research and establish drama in English language teaching as a generally accepted method.